On the verge of convergence : social stratification in Eastern Europe - Domański, Henryk (Central European University Press, 2000)
"Based upon comparative surveys and newly obtained data, Domanski's book provides a major contribution to the study of social transformation in Central and Eastern Europe after 1989. Focusing on Bulgaria, the Czech Republic, Hungary, Poland, Russia and Slovakia, the author provides substantial comparative information relating to social structure, mobility, inequality, lifestyle and economic stratification." "Applying the Erikson-Goldthorpe classification of class positions, Domanski presents fully comparable data to enable political comparisons to be made with other countries, especially those with firmly established free-market economies."--Jacket